Quantum π in Biomolecular Dynamics: Proteins as Nano-Quantum Fluids - Barack Ndenga (Publisher, 2025)
I propose a theoretical framework in which proteins are treated as nano-scale quantum fluids, whose internal dynamics are described by a Quantum π-field defined on their three-dimensional structure. Building on the hydrodynamic formulation of quantum mechanics (Madelung quantum hydrodynamics), I introduce a π-field that encodes local quantum coherence, phase topology, and energy flow within the protein, with particular emphasis on aromatic networks and electron/proton transfer channels. In this picture, proteins are not merely static folded structures or classical particles diffusing on an energy landscape; instead, they become quantum-coherent, fluid-like entities, with internal flows, vortices, and topological defects. Mutations and ligand binding are modeled as perturbations of the π-field, modifying local coherence, transport efficiency, and long-range allosteric communication. This approach unifies concepts from quantum hydrodynamics, protein energy landscapes, and bio-inspired quantum information flows, and it suggests a new class of computational tools for predicting mutation effects, functional hotspots, and dynamical pathways. To my knowledge, no existing biomolecular theory explicitly treats proteins as nano-quantum fluids governed by a π-field. I therefore present this framework as a novel conceptual and mathematical model for biomolecular dynamics.
Quantum π in Biomolecular Dynamics: Proteins as Nano-Quantum Fluids introduces a new theoretical and computational framework that models proteins as nano-scale quantum fluids, governed by a Quantum π-field defined over their structural and electronic landscape. This approach combines principles from quantum hydrodynamics, aromatic π-electron transport, protein energy landscapes, and topological coherence fields to describe biomolecular communication and internal energy flow. In this framework, the π-field acts as a coherence order parameter, capturing local quantum behavior, phase topology, and directional energy transport within proteins. Aromatic residues (Phe, Tyr, Trp, His) form high-π coherence networks, which behave as quantum transport channels capable of supporting long-range communication and allosteric regulation. Mutations are interpreted as π-defects, altering the coherence structure and re-routing quantum fluid flow inside the protein. This provides a new mechanistic explanation for mutation sensitivity, allosteric coupling, and functional propagation across distant sites. To my knowledge, this is the first scientific work proposing: a π-field formulation for biomolecular dynamics, a hydrodynamic quantum-fluid model of proteins, mutation-induced π-defects as functional perturbations, and high-π pathways as coherence and communication channels. This establishes a novel research direction referred to as Bio-Quantum π Dynamics (BQP Dynamics), bridging quantum physics, structural biology, and computational biochemistry. The dataset includes conceptual figures, theoretical descriptions, and supplementary material that illustrate π-field maps, aromatic coherence channels, and mutation-induced π-defects.